SONOGRAPHY TOUCHSTONE TESTING GOLD STANDARD RADIOGRAPHY FOR MEDICO-LEGAL AGE ESTIMATION IN LIVING: A PROSPECTIVE TRIPLE BLIND STUDY (Journal of Forensic Medicine & Toxicology, 2020)
Medico-legal age estimation involves varied professional of society. Researchers have been trying newer over existing methods to validate best which is scientifically substantial and adhering best ethics. Ultrasound being radiation free out of all modalities has been tried but for pediatric ages and at sites unsuitable for age estimation in adults which are of greater medico legal importance and occurrence. This prospective study compared ultrasound with radiographs at iliac crest which has appearance and fusion of epiphyses during 14th-22nd years making it anatomically relevant site to study by a radiation free method for age estimation. Results showed ultrasound was found to be more sensitive detecting smaller ossification centers at an advanced stage of appearance.
Keywords: Age estimation; Magnetic Resonance; Ultrasound; Iliac Crest; Epiphyseal Ossification